Development Project Sustainability Management (Study on Reservoir Development Projects in Sabu Raijua Regency) - Jacob WADU; Marthina Raga LAY; Emilia GIE; David Wilfrid RIHI; Jordan Indio MATA (International Journal of Environmental, Sustainability, and Social Science, 2023)
82.3% of the population of Sabu Raijua Regency work as farmers with a high level of need for water but the geographical conditions of Sabu Island are not able to support this activity because the majority consists of dry land with a percentage of 97.51% and the number of rainy days is approximately only 100 days per year so The Government of Sabu Raijua Regency built hundreds of ponds to provide for agricultural activities, but the weak sustainability of the reservoir development projects in Sabu Raijua Regency is a separate problem. The method used in this study is a descriptive method with a qualitative approach with a total of 76 people who were determined purposively then the primary and secondary data collected were analyzed using data analysis techniques from Creswell (2016). The sustainability of the pond development projects in Sabu Raijua Regency was analyzed using the Methodology in Sustainable Development Indicators (Department of Economic and Social Affairs, 2001:14). The inhibiting factors for the sustainability of the pond development project in Sabu Raijua Regency consist of a minimal budget, less effective institutional governance and climate and geographical conditions so that the authors formulate a model for the sustainability of the pond development project in Sabu Raijua Regency which includes 3 dimensions, namely the policy dimension, the resource dimension and the relationship dimension between institutions.